PH detection test paper as well as preparation method and application thereof

By adding cationic organic salts to the reagent loading layer of the pH detection test strip, a mesh protective film is formed to fix the pH color developer, which solves the problem of color developer leakage and uneven color development, and improves the accuracy and repeatability of the detection.

CN119640622APending Publication Date: 2025-03-18NANJING YIMU INTELLIGENT TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411781914.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the detection process, the pH color developer is prone to leakage and uneven color rendering, resulting in poor reading error and repetition.

Method used

By adding cationic organic salts to the reagent loading layer, a mesh protective film is formed to fix the pH color developer, thereby preventing it from leaking and contaminating the liquid to be tested, while improving the color development uniformity and detection accuracy.

Benefits of technology

Effectively prevent leakage and contamination of pH color developer, improve detection accuracy and repeatability, uniform color distribution, and test accuracy reaches more than 90%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides pH detection test paper and a preparation method and application thereof, the pH detection test paper comprises a substrate and a reagent loading layer, and the reagent loading layer is arranged on the substrate; the reagent loading layer contains a pH color developing agent and cationic organic salt. The preparation method of the pH detection test paper comprises the following steps: mixing a substrate and a solution containing a pH color developing agent, and carrying out first drying to obtain a first material; and then mixing the first material and the solution containing the cationic organic salt, and carrying out secondary drying to obtain the pH detection test paper. According to the method, the falling phenomenon of the pH color developing agent during detection can be avoided, color indication is uniform in the detection process, and the detection accuracy is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of pH test paper, and in particular to a pH test paper and a preparation method and application thereof. Background Art

[0002] As one of the important parameters for evaluating water quality, pH has a variety of mature testing technologies. Among them, the solid-state detection method - pH test paper has the advantages of low cost, maintenance-free, long shelf life, easy recycling, and adjustable size according to test needs. It uses a variety of pH indicators fixed on the test paper, drips the solution to be tested onto the test paper or directly contacts the solution with the test paper, and the test paper changes color and compares it with the standard colorimetric card to obtain the pH value of the solution.

[0003] The color development principle of pH test paper is based on the color-changing properties of acid-base indicators. Acid-base indicators are compounds that change color as the pH of a solution changes. Their molecules contain functional groups that can accept or release protons. When the solution is acidic, the proton concentration in the solution is high, and the indicator molecules will accept protons, causing changes in the molecular structure and thus changing color; when the solution is alkaline, the proton concentration in the solution is low, and the indicator molecules will release protons, causing changes in the molecular structure and also changing color.

[0004] The general method of making pH test paper is to directly immerse the test paper base paper into pH indicator solutions of different ratios for a period of time, and then make pH test paper of different specifications through processes such as rolling and drying.

[0005] However, during the test, as the liquid diffuses on the test paper, the indicator on the test paper dissolves and moves with the liquid, the color of the color-developing area on the test paper changes to different depths, and the dissolved indicator will fall into the test liquid to cause contamination, thereby resulting in reading errors and poor test paper test repeatability.

[0006] Therefore, it is necessary to develop a new type of pH test paper to solve the problems of indicator leakage and uneven color development. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a pH test paper and a preparation method and application thereof. By adding a cationic organic salt, the pH color developer can be prevented or limited from leaking into the liquid phase, and the pH color developer can be prevented from contaminating the liquid phase to be tested, and the test accuracy of the pH test paper can be further improved.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a pH test paper, the pH test paper comprising a substrate and a reagent loading layer, the reagent loading layer being arranged on the substrate; the reagent loading layer comprising a pH color developer and a cationic organic salt.

[0010] The present invention can fix the pH color developer on the substrate by adding a cationic organic salt, thereby avoiding leakage or transfer of the pH color developer during the detection process. Compared with the existing pH test paper, the present invention has the following characteristics:

[0011] A. Since the pH color developer may be transferred or leaked during the detection process of the pH test paper, and such transfer or leakage easily leads to uneven content of the pH color developer on the test paper, so that the accuracy of subsequent colorimetric detection is low, the present invention fixes the pH color developer by a cationic organic salt, which can ensure the uniformity of the distribution of the pH color developer on the test paper during the detection process, thereby improving the accuracy of the detection;

[0012] B. The present invention uses cationic organic salts for fixation, which can avoid the problem of pH color developer leaking into the liquid to be detected and causing contamination of the liquid to be detected;

[0013] C. The present invention can avoid the problem that the pH developer concentration on the original test paper is lower than the theoretical value due to the leakage of the pH developer, resulting in the color development concentration being lower than the actual data, and further improve the accuracy of the detection.

[0014] Preferably, the pH developer has an anionic group, and the cationic organic salt and the anionic group are connected to each other via an ionic bond.

[0015] The pH developer in the present invention has an anionic group and can be connected to the cationic organic salt through ionic bonds, and the cationic organic salt can form a mesh protective film on the surface of the reagent loading layer, that is, an ionic bond is formed between the mesh protective film and the pH developer, which firmly confines the pH developer between the substrate and the mesh protective film to avoid leakage of the pH developer.

[0016] Preferably, the surface of the reagent loading layer has a mesh protective film formed by a cationic organic salt, and the mesh protective film is connected to the pH color developer via ionic bonds and / or electrostatic adsorption.

[0017] The protective film of the present invention is a microscopic network structure, on which a plurality of connection points with the pH developer are distributed, thereby greatly improving the fixing effect of the pH developer.

[0018] Preferably, the pH developer penetrates into the substrate and adheres to the surface of the substrate.

[0019] Preferably, the substrate has cationic groups, and the pH developer forms a cross-linking system with the cationic groups on the substrate.

[0020] It is worth mentioning that there are two main points in the present invention to achieve the fixation of the pH color developer. One is that the pH color developer is interconnected with the mesh protective film formed by the cationic organic salt through ionic bonds, so that it does not move during the detection process; the other is that the pH color developer is fixed to the substrate through ionic bonds with the substrate itself, thereby coating and fixing the pH color developer on the substrate to achieve the fixation of the pH color developer.

[0021] Preferably, the mesh protective film has a thickness of 0.2 to 2 μm, for example, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.3 μm, 1.5 μm, 1.8 μm, 1.9 μm or 2.0 μm, etc.

[0022] Preferably, the cationic organic salt is a cationic polymer organic salt.

[0023] Preferably, the cationic organic salt comprises any one of polyquaternary ammonium salt, cationic polyacrylamide, chitosan or polydimethyldiallyl ammonium chloride or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of polyquaternary ammonium salt and cationic polyacrylamide, a combination of chitosan and cationic polyacrylamide, a combination of polyquaternary ammonium salt and chitosan, and a combination of polydimethyldiallyl ammonium chloride and chitosan.

[0024] For the selection of cationic organic salts, the following factors should be considered: the substrate of the test paper is generally made of cotton fiber, the main component of which is cellulose. There are a large number of -OH groups in the cellulose molecules, so it has excellent water absorption. The pH color developer molecules are attached to the surface of the cellulose molecules. If a thin polymer mesh protective film is attached to the cellulose surface at this time, it is necessary to reduce the dissolution of the indicator while maintaining the infiltration speed of the test paper.

[0025] In addition, since the pH color developer is usually in the form of anionic salts and carries anionic groups, and the polymer mesh protective membrane has cationic groups, the two can form an ionic bond to bind the pH color developer to the polymer mesh protective membrane, thereby effectively limiting the movement of the pH color developer with the liquid phase and achieving a uniform color development effect.

[0026] In order to achieve the above effects, the basic requirements for cationic organic salts are:

[0027] (1) Possessing a large number of cationic groups: There are a large number of groups such as ammonium groups in the polymer structure of cationic organic salts. These groups can not only provide cations to combine with the pH color developer with anions, but also increase the hydrophilicity of the polymer, thereby improving or maintaining the water absorption properties of the test paper itself.

[0028] (2) It has film-forming stability: it can form a thin film (protective layer) on the surface of cellulose, and this thin film (protective layer) can remain stable in water for a short period of time (at least within 10 to 40 seconds of use of the test paper) without dissolving.

[0029] According to the above-mentioned property requirements, the present invention preferably uses an organic salt containing an ammonium group, such as any one of polyquaternary ammonium salts, cationic polyacrylamide, chitosan or polydimethyldiallyl ammonium chloride, or a combination of at least two thereof as a cationic organic salt, which can better achieve the following key points: 1. It can be fixed to the substrate through hydrogen bonds; 2. It can form ionic bonds and / or electrostatic adsorption with the pH color developer; 3. It has excellent hydrophilic properties and can improve or maintain water wettability; 3. After film formation, it can remain stable and insoluble in water within the detection time.

[0030] Specifically, the quaternary ammonium salt group can be combined with the anion group in the pH color developer through an ionic bond; a large number of amide groups in polyacrylamide can form hydrogen bonds with the hydroxyl groups in the substrate, and can form a stable and uniform film layer on the surface of the test paper; the molecular structure of polydimethyldiallylammonium chloride is a cationic network structure, which can form hydrogen bonds with the fiber to form a stable film layer on its surface, and there is an electrostatic adsorption effect between the cation and the anion of the dye, thereby preventing the pH color developer from detaching from the surface of the substrate.

[0031] Preferably, the polyquaternium salt comprises polyquaternium-10.

[0032] The present invention preferably uses polyquaternium-10, the quaternary ammonium salt group in the molecule can be combined with the anion group in the pH developer through ionic bonds, thereby being fixed on the substrate, and a thin film can be formed on the surface of the substrate to prevent the pH developer from falling off.

[0033] Preferably, the weight average molecular weight of the cationic polyacrylamide is 60,000 to 1.2 million, for example, 60,000, 100,000, 120,000, 150,000, 200,000, 500,000, 1 million or 1.2 million, and preferably 100,000 to 600,000.

[0034] The weight average molecular weight of the cationic polyacrylamide is preferably 60,000 to 1.2 million, which can better ensure the hydrophilicity of the mesh protective film and the fixation effect on the pH color developer.

[0035] Preferably, the weight average molecular weight of the chitosan is 50,000 to 500,000, for example, 50,000, 55,000, 100,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000 or 500,000, and preferably 100,000 to 200,000.

[0036] The present invention preferably controls the weight average molecular weight of chitosan within the above range, which can ensure that the thickness of the mesh protective film is within a reasonable range, thereby better ensuring the reaction sensitivity of the test paper, and taking into account the adhesion ability to the substrate, ensuring the fixation effect of the pH color developer, and avoiding self-shedding in water or leakage of the pH color developer.

[0037] Preferably, the weight average molecular weight of the polydimethyldiallylammonium chloride is 100,000 to 500,000, for example, 100,000, 120,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000 or 500,000, and preferably 200,000 to 350,000.

[0038] The preferred weight average molecular weight of the polydimethyldiallylammonium chloride of the present invention is 100,000 to 500,000. Due to its strong cationicity, it has a strong binding force with the fiber surface and the indicator, and has the advantage of stably fixing the dye molecules.

[0039] Preferably, the pH developer comprises an anion indicator.

[0040] Preferably, the anion indicator is an anionic dye molecule.

[0041] Preferably, the anionic dye molecule comprises any one or a combination of at least two of cresol red, soap yellow, bromochlorophenol blue, chlorophenol red, bromocresol purple, bromothymol blue, phenol red, metacresol purple, phenolphthalein, alizarin yellow or indigo carmine, wherein a typical but non-limiting combination is a combination of cresol red and soap yellow, a combination of bromochlorophenol blue and soap yellow, a combination of cresol red and bromochlorophenol blue, a combination of chlorophenol red and soap yellow, a combination of cresol red and bromothymol blue, a combination of bromothymol blue and indigo carmine, a combination of phenol red and metacresol purple, a combination of alizarin yellow and soap yellow, a combination of indigo carmine and alizarin yellow. One indicator can be selected as an indicator of a narrow-range high-precision test paper according to demand, or two or more of them can be selected as indicators of a wide-range test paper.

[0042] Preferably, the loading density of the reagent loading layer on the pH test paper is 1.5-10 mg / cm 3 , for example, it can be 1.5 mg / cm 3 , 2mg / cm 3 , 2.5mg / cm 3 、3mg / cm 3 , 4mg / cm 3 , 4.5mg / cm 3, 5mg / cm 3 , 6mg / cm 3 、6.5mg / cm 3 , 7mg / cm 3 , 8mg / cm 3 , 9mg / cm 3 or 10mg / cm 3 wait.

[0043] In a second aspect, the present invention provides a method for preparing the pH test paper according to the first aspect, the preparation method comprising:

[0044] The substrate and the solution containing the pH developer are mixed, and then subjected to a first drying process to obtain a first material; and then the first material and the solution containing the cationic organic salt are mixed, and then subjected to a second drying process to obtain the pH test paper.

[0045] The preparation method provided in the second aspect of the present invention can produce the pH test paper described in the first aspect, has excellent performance, simple preparation process and broad application prospects. The present invention requires first soaking the pH developer and then soaking the solution containing the cationic organic salt, and fixing the pH developer inside with a mesh protective film.

[0046] The present invention has no particular limitation on the solid-to-liquid ratio of the substrate and the solution in the above process, and any solid-to-liquid ratio known to those skilled in the art may be used as long as the substrate is fully wetted.

[0047] Preferably, the first drying and the second drying are each independently vacuum drying.

[0048] Preferably, the mixed substrate and the solution containing the pH developer are immersed for 8 to 15 seconds, for example, 8 seconds, 9 seconds, 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds or 15 seconds, but are not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0049] Preferably, the first material and the solution containing the cationic organic salt are mixed and infiltrated for 25 to 35 seconds, for example, 25 seconds, 27 seconds, 28 seconds, 29 seconds, 30 seconds, 31 seconds, 32 seconds, 33 seconds, 34 seconds or 35 seconds, but are not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0050] Preferably, the concentration of the pH color developer in the solution containing the pH color developer is 0.25 to 1.5 mM, for example, it can be 0.25 mM, 0.39 mM, 0.53 mM, 0.67 mM, 0.81 mM, 0.95 mM, 1.09 mM, 1.23 mM, 1.37 mM or 1.5 mM, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 0.75 to 1.25 mM.

[0051] Preferably, the solvent in the solution containing the pH color developer includes ethanol and water, wherein the volume ratio of ethanol to water is 0.25:1 to 9:1, for example, it can be 0.25:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 0.85:1 or 0.9:1, etc., preferably 1.25:1 to 9:1.

[0052] Preferably, the solution containing the pH developer also contains a pH adjuster.

[0053] The present invention has no special requirements for the pH regulator. Different pH values ​​need to be controlled according to different pH-containing color developers. For example, the pH regulator can be selected from dilute hydrochloric acid and NaOH solution.

[0054] Preferably, the concentration of the cationic organic salt in the solution containing the cationic organic salt is 0.1wt% to 3.0wt%, for example, it can be 0.1wt%, 0.5wt%, 0.8wt%, 1.1wt%, 1.4wt%, 1.8wt%, 2.1wt%, 2.4wt%, 2.7wt% or 3.0wt%, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 0.3wt% to 1.0wt%.

[0055] The present invention preferably controls the concentration of the cationic organic salt within the above range, which can better control the viscosity of the solution containing the cationic organic salt within the range of 80 to 600 mPa·s, thereby ensuring the adhesion of the mesh protective film on the substrate and the reaction sensitivity of the test paper, while improving the detection accuracy and avoiding the transfer and leakage of the pH color developer.

[0056] Preferably, the solvent of the solution containing the cationic organic salt comprises water.

[0057] Preferably, the solution containing the cationic organic salt further comprises a pH regulator. Depending on the pH to be regulated, the pH regulator can be selected from dilute hydrochloric acid and NaOH solution.

[0058] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0059] The substrate is first soaked in ethanol and / or water solution with a pH color developer concentration of 0.25-1.5 mM, and excess water is squeezed out and dried to obtain a first material.

[0060] Then, the first material is soaked in an aqueous solution containing 0.1 wt% to 3.0 wt% of a cationic organic salt, excess water is squeezed out, and the material is dried to obtain the pH test paper.

[0061] The present invention has no special limitation on the substrate, and any substrate for test paper known to those skilled in the art can be used, or it can be adjusted according to actual conditions, for example, cellulose paper, filter paper or absorbent cotton paper can be used.

[0062] In a third aspect, the present invention provides an application of the pH test paper described in the first aspect in pH detection, preferably in liquid phase pH detection.

[0063] The pH test paper provided in the third aspect of the present invention can be preferably used in pH detection.

[0064] Compared with the prior art, the present invention has at least the following beneficial effects:

[0065] (1) The pH test paper provided by the present invention forms a mesh protective film by adding cationic organic salts, and the cationic organic salts "bridge" between the pH color developer and the paper cellulose, and cross-link with the pH color developer molecules and cellulose to form a highly diversified cross-linking system. The pH color developer will be fixed between the test paper fibers and the mesh protective film, so that the pH color developer and the paper are more firmly combined to prevent the indicator molecules from falling off the fibers. At the same time, the cationic organic salt forms a three-dimensional mesh film on the fiber surface, which can enclose the indicator inside, allowing water molecules to penetrate into the test process to make the indicator color, but not allowing the indicator molecules to fall off from the fibers into the water, so that the test paper color is uniform and does not contaminate the test liquid.

[0066] (2) When the pH test paper provided by the present invention is used to detect actual water samples, the color distribution on the test paper surface is uniform, and the color changes more obviously with the index to be tested, which can significantly improve the resolution and recognition accuracy of the color card, and the test accuracy is above 90% and the resolution is within 0.4.

[0067] (3) When the pH test paper provided by the present invention detects pH, due to the presence of the mesh protective film, the contact time between the test paper and the test solution can be increased. The test paper is preferably immersed in the water phase for a long time of more than 1 minute without decolorization, so that the hydrogen ions or hydroxide ions in the water are enriched on the test paper, thereby enhancing the color response of the test paper, the color development effect is stronger, and the naked eye resolution and recognition accuracy of the color card are significantly improved. DETAILED DESCRIPTION

[0068] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0069] Example 1

[0070] This embodiment provides a pH test paper, the pH test paper comprising a substrate and a reagent loading layer, the reagent loading layer being arranged on the substrate;

[0071] The reagent loading layer contains a pH developer and a cationic organic salt; the pH developer has an anionic group, and the cationic organic salt and the anionic group are connected by an ionic bond. The surface of the reagent loading layer has a mesh protective film formed by the cationic organic salt; the substrate has a cationic group, and the pH developer forms a cross-linking system with the cationic group on the substrate.

[0072] The thickness of the mesh protective film is 0.8 μm. The cationic organic salt is polyquaternium-10. The pH color developer is phenol red.

[0073] The loading density of the reagent loading layer on the pH test paper is 6.6 mg / cm 3 .

[0074] The preparation method of the pH test paper comprises the following steps:

[0075] The cellulose test paper was first soaked in an ethanol and water solution (volume ratio 7:3) of 1 mM phenol red at pH 7.9 for 10 seconds, and then the excess water was squeezed out and dried to obtain the first material;

[0076] Then, the first material is immersed in an aqueous solution (viscosity of 200 mPa·s) containing 0.5 wt % of polyquaternium-10 for 30 seconds, and the excess water is squeezed out and dried to obtain the pH test paper.

[0077] Example 2

[0078] This embodiment provides a pH test paper, the pH test paper comprising a substrate and a reagent loading layer, the reagent loading layer being arranged on the substrate;

[0079] The reagent loading layer contains a pH developer and a cationic organic salt; the pH developer has an anionic group, and the cationic organic salt and the anionic group are connected by an ionic bond. The surface of the reagent loading layer has a mesh protective film formed by the cationic organic salt; the substrate has a cationic group, and the pH developer forms a cross-linking system with the cationic group on the substrate.

[0080] The thickness of the mesh protective film is 1.0 μm. The cationic organic salt is cationic polyacrylamide with a molecular weight of 200,000. The pH color developer is cresol red.

[0081] The loading density of the reagent loading layer on the pH test paper is 6.2 mg / cm 3 .

[0082] The preparation method of the pH test paper comprises the following steps:

[0083] The cellulose test paper was first soaked in an ethanol and water solution (volume ratio 7:3) of 1 mM cresol red at pH 8.2 for 10 seconds, and then the excess water was squeezed out and dried to obtain the first material;

[0084] Then, the first material is immersed in an aqueous solution (viscosity of 260 mPa·s) containing 0.8 wt % of a cationic polyacrylamide with a molecular weight of 200,000 for 30 seconds, and the excess water is squeezed out and dried to obtain the pH test paper.

[0085] Example 3

[0086] This embodiment provides a pH test paper, the pH test paper comprising a substrate and a reagent loading layer, the reagent loading layer being arranged on the substrate;

[0087] The reagent loading layer contains a pH developer and a cationic organic salt; the pH developer has an anionic group, and the cationic organic salt and the anionic group are connected by an ionic bond. The surface of the reagent loading layer has a mesh protective film formed by the cationic organic salt; the substrate has a cationic group, and the pH developer forms a cross-linking system with the cationic group on the substrate.

[0088] The thickness of the mesh protective film is 1.9 μm. The cationic organic salt is chitosan, and the molecular weight is 100,000. The pH color developer is bromothymol blue.

[0089] The loading density of the reagent loading layer on the pH test paper is 8.5 mg / cm 3 .

[0090] The preparation method of the pH test paper comprises the following steps:

[0091] The cellulose test paper was first soaked in an ethanol and water solution (volume ratio 2:8) of 1.25 mM bromothymol blue at pH 7.0 for 15 seconds, and then the excess water was squeezed out and dried to obtain a first material;

[0092] Then, the first material is immersed in an aqueous solution (viscosity of 600 mPa·s) containing 3.0 wt % chitosan with a molecular weight of 100,000 for 25 seconds, and the excess water is squeezed out and dried to obtain the pH test paper.

[0093] Example 4

[0094] This embodiment provides a pH test paper, the pH test paper comprising a substrate and a reagent loading layer, the reagent loading layer being arranged on the substrate;

[0095] The reagent loading layer contains a pH developer and a cationic organic salt; the pH developer has an anionic group, and the cationic organic salt and the anionic group are connected by an ionic bond. The surface of the reagent loading layer has a mesh protective film formed by the cationic organic salt; the substrate has a cationic group, and the pH developer forms a cross-linking system with the cationic group on the substrate.

[0096] The thickness of the mesh protective film is 1.8 μm. The cationic organic salt is polydimethyldiallylammonium chloride with a molecular weight of 300,000. The pH color developer is m-cresol violet.

[0097] The loading density of the reagent loading layer on the pH test paper is 5.3 mg / cm 3 .

[0098] The preparation method of the pH test paper comprises the following steps:

[0099] The cellulose test paper was first soaked in an ethanol and water solution (volume ratio 9:1) of 0.75 mM m-cresyl violet at pH 8.32 for 8 seconds, and then the excess water was squeezed out and dried to obtain the first material;

[0100] Then, the first material is immersed in an aqueous solution (viscosity of 560 mPa·s) containing 3.0 wt % of polydimethyldiallylammonium chloride with a molecular weight of 300,000 for 35 seconds, and the excess water is squeezed out and dried to obtain the pH test paper.

[0101] Example 5

[0102] This embodiment provides a pH test paper. The pH test paper is the same as that of Embodiment 2 except that the molecular weight of the cationic polyacrylamide is 80,000, and will not be described in detail here.

[0103] Example 6

[0104] This embodiment provides a pH test paper. The pH test paper is the same as that of Embodiment 3 except that the molecular weight of chitosan is 80,000, and will not be described in detail here.

[0105] Example 7

[0106] This embodiment provides a pH test paper. The pH test paper is the same as that of Embodiment 4 except that the molecular weight of polydimethyldiallylammonium chloride is 150,000, and the details are not described again.

[0107] Example 8

[0108] This embodiment provides a pH test paper. The pH test paper is the same as that of Embodiment 2 except that the molecular weight of the cationic polyacrylamide is 1.3 million, and will not be described in detail here.

[0109] Example 9

[0110] This embodiment provides a pH test paper. The pH test paper is the same as that of Embodiment 3 except that the molecular weight of chitosan is 600,000, and will not be described in detail here.

[0111] Example 10

[0112] This embodiment provides a pH test paper. The pH test paper is the same as that of Embodiment 4 except that the molecular weight of polydimethyldiallylammonium chloride is 600,000, and details thereof will not be repeated here.

[0113] Embodiment 11

[0114] This embodiment provides a pH test paper, which is the same as that of Embodiment 1 except that 0.5 wt % of polyquaternium-10 is replaced by 0.05 wt % of polyquaternium-10, and will not be described in detail herein.

[0115] Example 12

[0116] This embodiment provides a pH test paper, which is the same as that of Embodiment 1 except that 0.5 wt % of polyquaternium-10 is replaced by 3.5 wt % of polyquaternium-10, and will not be described in detail here.

[0117] Embodiment 13

[0118] This embodiment provides a pH test paper. The pH test paper is the same as that in Embodiment 1 except that polyquaternium-10 is replaced by trimethylammonium bromide, and the details are not described again.

[0119] Comparative Example 1

[0120] This comparative example provides a pH test paper, which is the same as Example 1 except that polyquaternium-10 is replaced by sodium carboxymethyl cellulose, and is not described in detail here.

[0121] Comparative Example 2

[0122] This comparative example provides a pH test paper, which is the same as Example 1 except that polyquaternium-10 is replaced by hydroxyethyl cellulose with a molecular weight of 20,000, and will not be described in detail here.

[0123] Comparative Example 3

[0124] This comparative example provides a pH test paper, which is the same as Example 1 except that polyquaternium-10 is replaced by sodium hyaluronate with a molecular weight of 80,000, and will not be described in detail here.

[0125] Test method: After the test paper is prepared, cut it into 5mm*5mm squares and stick it on PVC cut into long strips. Prepare pH standard solution according to the gradient of 0.2pH interval and measure its pH with a pH meter.

[0126] Use the prepared test papers to test the pH standard solutions respectively. Immerse the test paper strips in the test solution for 3 seconds, then take them out and shake off excess water. Extract the color of the test paper within 30 seconds and draw a standard color card.

[0127] The pH standard solution was tested with the prepared pH test paper. The tester did not know the specific pH value and read the value by comparing the color card. If the reading shown on the color card was the same as the pH of the solution being tested, the comparison was considered correct, otherwise it was wrong. Three groups were tested in parallel.

[0128] Soak the test paper in the solution for 1 minute, take it out and observe whether the color of the test paper falls off.

[0129] The test results of the above embodiments and comparative examples are shown in Table 1.

[0130] Table 1

[0131] pH detection range Resolution Test accuracy Is it discolored after soaking for 1 minute? Example 1 6.6-8.4 0.4 91% no Example 2 7.0-9.0 0.4 93% no Example 3 6.0-8.0 0.2 98% no Example 4 7.4-9.0 0.2 92% no Example 5 7.0-9.0 0.4 86% no Example 6 6.0-8.0 0.2 88% no Example 7 7.4-9.6 0.2 84% no Example 8 7.0-9.0 0.4 85% yes Example 9 6.0-8.0 0.2 89% yes Example 10 7.4-9.0 0.2 82% yes Embodiment 11 6.6-8.4 0.4 81% yes Example 12 6.0-8.0 0.2 80% yes Embodiment 13 7.4-9.0 0.2 79% yes Comparative Example 1 6.6-8.4 0.4 70% yes Comparative Example 2 6.6-8.4 0.4 76% yes Comparative Example 3 6.6-8.4 0.4 78% yes

[0132] From Table 1, we can see the following points:

[0133] (1) It can be seen from Examples 1 to 4 that the pH test paper provided by the present invention can significantly prolong the contact time between the pH test paper and the test solution by providing a cationic organic salt on the reagent loading layer to form a mesh protective film. The test paper will not decolorize when immersed in the aqueous phase for a long time of more than 1 min. Moreover, the resolution is within 0.4, the test accuracy is more than 90%, and the detection effect is good.

[0134] (2) It can be seen from Examples 2 to 4 and Examples 5 to 10 that the present invention controls the weight average molecular weight of the cationic organic salt within a reasonable range, which can, on the one hand, avoid the situation where the detection resolution is reduced due to the excessive molecular weight; on the other hand, it can ensure the formation of a sufficient mesh protective film, thereby slowing down the dissolution rate of the pH color developer, thereby extending the maximum immersion time and improving the detection effect.

[0135] (3) From Example 1 and Examples 11 to 12, it can be seen that the concentration of polyquaternium-10 in the aqueous solution of polyquaternium-10 in Example 1 is 0.5wt%. Compared with the concentrations of polyquaternium-10 in Examples 11 to 12, which are 0.05wt% and 3.5wt%, respectively, the test accuracy of Example 1 is 91%, and no decolorization occurs after immersion for 1 min. The test accuracy in Examples 11 to 12 is only 81% and 80%, respectively, and decolorization occurs after immersion for 1 min. This shows that the present invention preferably controls the concentration of the cationic organic salt within a reasonable range, which can better extend the immersion time of the pH test paper and has a higher test accuracy.

[0136] (4) It can be seen from Example 1 and Example 13 that in Example 13, trimethylammonium bromide is used as a cationic organic salt, which is not a high molecular polymer. Compared with Example 1, its detection accuracy is significantly reduced to 79%, and obvious discoloration occurs after immersion for 1 minute. This shows that the present invention can form a mesh protective film and fix the pH color developer inside by using an anionic organic salt of a high molecular material, thereby improving the detection accuracy and the immersion resistance of the test paper.

[0137] (5) It can be seen from Example 1 and Comparative Examples 1 to 3 that the use of non-ionic cellulose or anionic salts not only fails to protect the pH color developer, but also reduces the detection accuracy to below 78%. This shows that the present invention uses cationic salts to form a mesh protective film on the surface of the substrate, which can protect the pH color developer and improve the detection accuracy at the same time.

[0138] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A pH test paper, characterized in that The pH test paper comprises a substrate and a reagent loading layer, wherein the reagent loading layer is arranged on the substrate; The reagent loading layer contains a pH color developing agent and a cationic organic salt.

2. The pH test paper according to claim 1, characterized in that The pH developer has an anionic group, and the cationic organic salt and the anionic group are connected to each other by an ionic bond; And / or, the surface of the reagent loading layer has a mesh protective film formed by a cationic organic salt; And / or, the substrate has cationic groups, and the pH developer forms a cross-linking system with the cationic groups on the substrate.

3. pH test paper according to claim 2, characterized in that, The mesh protective film has a thickness of 0.2 to 2 μm.

4. The pH test paper according to any one of claims 1 to 3, characterized in that The cationic organic salt is a cationic polymer organic salt; The cationic organic salt includes any one of polyquaternary ammonium salt, cationic polyacrylamide, chitosan or polydimethyldiallylammonium chloride or a combination of at least two thereof.

5. The pH test paper according to claim 4, characterized in that The polyquaternium salt includes any one of polyquaternium-10, polyquaternium-9, polyquaternium-14 or polyquaternium-17, or a combination of at least two thereof; And / or, the weight average molecular weight of the cationic polyacrylamide is 60,000 to 1.2 million; And / or, the weight average molecular weight of the chitosan is 50,000 to 500,000; And / or, the weight average molecular weight of the polydimethyldiallylammonium chloride is 100,000 to 500,000.

6. The pH test paper according to claim 1, characterized in that The pH color developer includes an anion indicator; the anion indicator is an anionic dye molecule.

7. The pH test paper according to any one of claims 1 to 3, characterized in that: The loading density of the reagent loading layer on the pH test paper is 1.5-10 mg / cm 3 .

8. A method for preparing a pH test paper according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The substrate and the solution containing the pH developer are mixed, and then subjected to a first drying process to obtain a first material; and then the first material and the solution containing the cationic organic salt are mixed, and then subjected to a second drying process to obtain the pH test paper.

9. The preparation method according to claim 8, characterized in that: The concentration of the pH color developer in the solution containing the pH color developer is 0.25 to 1.5 mM; And / or, the solvent in the solution containing the pH developer comprises ethanol and water, wherein the volume ratio of ethanol to water is 0.25:1 to 9:1; And / or, the concentration of the cationic organic salt in the solution containing the cationic organic salt is 0.1 to 3.0 wt %.

10. Use of the pH test paper according to any one of claims 1 to 7 in pH detection.

Citation Information

Patent Citations

  • Test paper for detecting pH and nitrite and preparation method thereof

    CN118566208A

  • Pigment particles for ph sensor

    JP1995191013A

  • Test paper and method for manufacturing test paper

    JP2024034335A

Cited By

  • Ph test strip, and preparation method therefor and use thereof

    WO2026118400A1